2020
DOI: 10.5539/gjhs.v12n9p76
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study Exploring Motivators and Barriers to Physical Activity Participation Among Hospital Workers

Abstract: The workplace is an ideal setting to implement an effective health-promoting program. Insufficient information exists regarding the motivators and barriers to physical activity among working adults in Qatar. Therefore, this study aimed to identify the motivators and barriers to physical activity among adults in a healthcare setting. This cross-sectional study was conducted in an orthopaedic and sports medicine hospital. The participants were Qatari and non-Qatari adult staff (n = 100), who were recruited by wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the other hand, the women who carried out no PA during the lockdown were older than those who did PA frequently. This phenomenon could be down to several causes, such as the greater age, the students could most probably have parallel work tasks, which makes free time available to carry out PA more difficult [ 44 , 45 ]. However, the women who did no type of PA at all were older and lived with fewer people (it is probable that, in accordance with that found in other studies, older students prefer to live alone or with fewer people in the latter years of their academic studies, which would justify the few people with whom they live) than those who carried out strength exercises.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the women who carried out no PA during the lockdown were older than those who did PA frequently. This phenomenon could be down to several causes, such as the greater age, the students could most probably have parallel work tasks, which makes free time available to carry out PA more difficult [ 44 , 45 ]. However, the women who did no type of PA at all were older and lived with fewer people (it is probable that, in accordance with that found in other studies, older students prefer to live alone or with fewer people in the latter years of their academic studies, which would justify the few people with whom they live) than those who carried out strength exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to the interventions were also reported as limitations in four of the intervention studies (Tomar and Allen, 2016a;Al Saweer, Salehi and Al Tiho, 2017;Al-Mohannadi et al, 2019;Altwaijri et al, 2019). The two most commonly reported barriers to physical activity in workplace were "work demand" and "hot weather" as noted by a cross-sectional study (Al-Mohannadi et al, 2020) and also reported in the peer-reviewed brief report (Alkhatib, 2015). "Hot weather" was also a main limiting factor in two intervention studies (Al Saweer, Salehi and Al Tiho, 2017;Al-Mohannadi et al, 2019).…”
Section: Motivators and Barriers To Physical Activity In The Workplacementioning
confidence: 93%
“…Qualitative findings in relation to motivators and barriers to exercise were reported in two of the non-intervention studies (Alkhatib, 2015;Al-Mohannadi et al, 2020). Barriers to the interventions were also reported as limitations in four of the intervention studies (Tomar and Allen, 2016a;Al Saweer, Salehi and Al Tiho, 2017;Al-Mohannadi et al, 2019;Altwaijri et al, 2019).…”
Section: Motivators and Barriers To Physical Activity In The Workplacementioning
confidence: 98%
See 2 more Smart Citations